Learning Pro Tools 11 - Godfrey, Joe (InfiniteSkills, 2013)
"In this video based Pro Tools 11 training course, expert trainer Joe Godfrey teaches you the fundamentals of using this digital audio workstation software. Pro Tools 11 brings you the power of 64bit recording and mixing to your computer - with retooled audio and video engines in this latest version from Avid. This course is designed for the absolute beginner, and no prior experience with Pro Tools is required. Joe starts by introducing you to the basic skills you will need, such as working with dialog, music and sound effects. You will learn to edit music tracks, work with elastic audio and how to utilize MIDI in Pro Tools. This tutorial also covers more advanced features such as beat making, composing using virtual instruments, scoring to picture and tracking live instruments. You finish off this video based training course with an in-depth look at Mixing and Automation. Once you have completed this video tutorial for Avid Pro Tools 11, you will have a solid understanding of the fundamentals of recording and mixing using this popular software. Working files are included, allowing you to follow along with the author throughout the lessons."--Resource description page.